Text-to-speech synthesis with an Indian language perspective. (2015) - Panda, Soumya Priyadarsini; Nayak, Ajit Kumar; Patnaik, Srikanta
Speech synthesis deals with artificial production of speech, and a Text-to-Speech (TTS) system in this aspect converts natural language text into a corresponding spoken waveform or speech. There have been sufficient successes today in the area of speech and natural language processing that suggest that these technologies will continue to be a major area of research and development in creating intelligent systems. In this paper we provide an overview of the TTS synthesis technology along with details of the phases involved. The thrust has been given to explore the usefulness of this technique in designing a TTS system for Indian languages. This paper also focuses on some of the open research issues where work in this area may further be done.